Hermeneutic Uncertainty and Prejudice - Wallaert, Ineke (Meta, 2016)
Hermeneutic uncertainty is an inherent part of the art of translation, and its consequences are ineluctable features of translation products. In this article I support the claim that the teaching and practice of translation do not escape the social responsibility which resides in clearly declaring and acknowledging the existence of hermeneutic uncertainty. Investigating how Heideggerian hermeneutics led to Gadamer’s development of the concept of hermeneutic prejudice. I will show that the philosophical description of how this prejudice functions can be a useful part of the pedagogical materials presented by translation teachers, and can help students to approach ambiguous or difficult source text elements more confidently. Such hermeneutic consciousness-raising can also be applied to published translations, where it can be tested to reveal how translators have dealt with specific instances of hermeneutic uncertainty. The case studied here is a pair of terms occurring in Walter Benjamin’s Die Aufgabe des Übersetzers, chosen mainly for its ubiquitous presence in the field of translation studies. The story of how French and English translations differ in their understanding of this specific hermeneutic difficulty will be used to investigate the extent to which translators acknowledge (or ignore) the existence of hermeneutic uncertainty by allowing it to enter their translations or by discarding it from them.